Perception analysis of living environment at Taman Melati residential area - Kadar Hamsa, Abdul Azeez; Masao, Miura; Shuhei, Inokuma; Yosuke, Nishimura (Faculty of Built Environment, University of Malaya, 2010)
Rapid physical development in a residential area will deteriorate living environment of the residents especially if it takes place haphazardly without applying adequate planning guidelines. It will, eventually, exert more pressure on physical infrastructure of the area. As a result, residents of the area will be subjected to dissatisfaction on the present supporting infrastructure as the demand exceeds the supply. Evidently, it may lead to poor living conditions of the area, which ultimately slow the progressiveness of the society to achieve the quality of living standards. This paper investigates residents’ perceptions on present living environmental setting at Taman Melati residential area in Kuala Lumpur. Questionnaire survey was administered to determine the perceptions of the residents on physical environmental parameters such as air, noise, streetlight illuminance, and traffic volume. The level of satisfaction of the residents on the living environment had showed nearly 64% of the respondents expressed “satisfied strongly” or “satisfied”. The level of willingness of the residents to stay further continuously at Taman Melati indicates about 56% of the respondents expressed “strongly willing” or “willing”. It is also seen that the overall satisfaction level of the residents on the living environment was high albeit satisfaction level on individual physical environmental parameters was low.